2017
DOI: 10.1101/gad.301036.117
|View full text |Cite
|
Sign up to set email alerts
|

m6A mRNA modifications are deposited in nascent pre-mRNA and are not required for splicing but do specify cytoplasmic turnover

Abstract: Understanding the biologic role of N 6 -methyladenosine (m 6 A) RNA modifications in mRNA requires an understanding of when and where in the life of a pre-mRNA transcript the modifications are made. We found that HeLa cell chromatin-associated nascent pre-mRNA (CA-RNA) contains many unspliced introns and m 6 A in exons but very rarely in introns. The m 6 A methylation is essentially completed upon the release of mRNA into the nucleoplasm. Furthermore, the content and location of each m 6 A modification in stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
535
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 486 publications
(668 citation statements)
references
References 74 publications
43
535
3
Order By: Relevance
“…Although methylation of the target introns has not been demonstrated, this suggests existence of a more general link between intron methylation, retention, and nuclear decay (Kilchert et al, 2015). Building on this mechanism, we also found that a fraction of TARBP2 is associated with chromatin, and therefore it is plausible that TARBP2 promotes intron methylation co-transcriptionally, consistent with a recent report that m 6 A marks are deposited on nascent pre-mRNA (Ke et al, 2017). We speculate that the mode of TARBP2-dependent post-transcriptional regulation we describe here may be advantageous because it allows for the fast decoupling of expression of the TARBP2 regulon from transcriptionally controlled levels.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Although methylation of the target introns has not been demonstrated, this suggests existence of a more general link between intron methylation, retention, and nuclear decay (Kilchert et al, 2015). Building on this mechanism, we also found that a fraction of TARBP2 is associated with chromatin, and therefore it is plausible that TARBP2 promotes intron methylation co-transcriptionally, consistent with a recent report that m 6 A marks are deposited on nascent pre-mRNA (Ke et al, 2017). We speculate that the mode of TARBP2-dependent post-transcriptional regulation we describe here may be advantageous because it allows for the fast decoupling of expression of the TARBP2 regulon from transcriptionally controlled levels.…”
Section: Discussionsupporting
confidence: 76%
“…A methylation impacts intron retention and RNA stability Recently, it was shown that RNA methylation can occur co-transcriptionally, and m 6 A marks can be detected in chromatin-associated RNA (Ke et al, 2017). Analysis of these chromatin-associated RNA m 6 A marks (CA-m 6 A) revealed that there is a significant enrichment of TARBP2-bound introns among chromatin-associated methylated introns ( Figure S3A).…”
Section: Tarbp2-dependent Mmentioning
confidence: 98%
See 2 more Smart Citations
“…
AbstractBy using a cell fraction technique that separates chromatin associated nascent RNA, newly completed nucleoplasmic mRNA and cytoplasmic mRNA, we have shown (Ke et al 2017) that residues in exons are methylated (m 6 A) in nascent pre-mRNA and remain methylated in the same exonic residues in nucleoplasmic and cytoplasmic mRNA. Thus, there is no evidence of a substantial degree of demethylation in mRNA exons that would correspond to so-called "epigenetic" demethylation.
…”
mentioning
confidence: 99%